Maternal obstructive sleep apnea and neonatal birth outcomes in a population based sample - Bourjeily, Ghada (Sleep Med, 2019)
OBJECTIVE: Evaluate the association of OSA with birth outcomes including the risk of congenital anomalies and the need for a higher level of clinical care at delivery. METHODS: Population-based study that linked newborn records with maternal records. Data from 95 perinatal centers across all geographic census divisions of the U.S. of women with a delivery diagnosis from 2010 to 2014 whose records could be linked to the corresponding newborn record. An International Classification of Diseases, ninth Revision (ICD-9) code for sleep apnea was used to identify exposure and outcome variables. Univariate and multivariate logistic regression analyses were performed with a model that included substance use, obesity, diabetes, maternal co-morbidities, and pregnancy complications. RESULTS: In this study, 1,423,099 maternal records were linked to live newborn records. OSA was associated with a higher risk for congenital anomalies in offspring (aOR 1.26, 1.11 to 1.43), with the highest risk being that of musculoskeletal anomalies (aOR 1.89, 1.16 to 3.07) after adjusting for comorbidities and potential teratogens. Neonates born to mothers with OSA were more likely to be admitted to the intensive care unit (25.3% vs. 8.1%, p < 0.001), require resuscitation (aOR 2.76, 1.35 to 5.64) and have a longer hospital stay (aOR 2.25, 1.85 to 2.65). CONCLUSIONS: Although our study does not establish causation, it is the first to demonstrate a higher risk of congenital anomalies and resuscitation at birth in neonates of mothers with OSA, emphasizing the importance of identifying OSA in pregnant women and women of reproductive age.